HUBUNGAN PENETAPAN HARGA KAMAR DENGAN KEPUTUSAN KONSUMEN UNTUK MENGGUNAKAN JASA KAMAR DI HOTEL ALANA PADANG - Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2013)
This study aimed to analyze (1) consumer response to pricing on hotel rooms Alana Padang, (2) the consumer's decision to use room service at the hotel Alana Padang and (3) the relationship with the room price fixing in the consumer's decision to use Padang Alana hotel room service. The study population was a visitor Alana Hotel Padang April 2012 sampling technique using accidental sampling with a sample size of 83 rooms based on the number of occupancy in April 2012 From the results obtained the following conclusions: (1) pricing is carried out by the Hotel Alana Padang has been in accordance with the facilities provided, equipment room and the hotel location is strategic, and (2) There is a positive and significant relationship between the pricing of the consumer's decision to use the services of Alana Hotel rooms at Padang.Key Words: hotel, room pricing, costumer's decision.